Pengaruh Intervensi Family Empowerment terhadap Lama Rawat Pasien Skizofrenia - Lenni Afriani Batubara; Siti Saidah Nasution; Zulhaida Lubis (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effect of Family Empowerment (Psychoeducation) intervention on the length of stay of schizophrenic patients. This research method is quantitative research with a quasi-experimental research design with a control group. Research sampling technique with accidental sampling. The number of samples was 80 respondents from February to March 2023, schizophrenic patients at the Prof. Mental Hospital. Dr. Muhammad Ildrem Medan. The research instrument used a questionnaire and a long patient record form. Univariate and bivariate data analysis with the Mann-Whitney test. The results showed the average length of stay of schizophrenic patients at the Prof. Mental Hospital. Dr. Muhammad Ildrem 10-30 days. The statistical test results showed that there was an effect of Family Empowerment (Psychoeducation) intervention on the length of stay of schizophrenic patients at the Prof. Mental Hospital. Dr. Muhammad Ildrem. In conclusion, there is an effect of Family Empowerment (Psychoeducation) intervention on the length of stay of schizophrenic patients. Keywords: Family Empowerment, Length of Stay, Schizophrenia.